Policy responses to a dark side of the integration of regions - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
In his paper I study policy responses to an increase in post-merger distress. I consider the integration of regions as a merger of populations which I view as a revision of social space, and I identify the effect of the merger on aggregate distress. The paper is based on the premise that the merger of groups of people alters their social landscape and their comparators. Employing a specific measure of social distress that is based on the sensing of relative deprivation, a merger increases aggregate distress: the social distress of a merged population is greater than the sum of the social distress of the constituent populations when apart. In response, policies are enacted to ensure that aggregate distress and/or that of individuals does not rise after a merger. I consider two publicly-financed, cost-effective policies designed so as not to reduce individuals' incomes: a policy that reverses the negative effect of the merger on the aggregate level of relative deprivation, bringing it back to the sum of the pre-merger levels of aggregate relative deprivation of the two populations when apart; and a policy that is aimed at retaining the relative deprivation of each individual at most at its pre-merger level. These two policies are developed as algorithms. Numerical examples illustrate the application of the algorithms.
urn:nbn:de:bsz:21-opus-60360
Keywords: D04; D63; F55; H53; P51; 330; merger of populations; revision of social space; aggregate relative deprivation; societal distress; policy responses